Pneumocephalus associated with Bacteroides fragilis meningitis - Parmar Malvinder (Journal of Postgraduate Medicine, 2004)
Gas within the intracranial cavity (pneumocephalus) commonly results from trauma or after surgery and rarely from infection by gas-forming organisms. The presence of pneumocephalus in the absence of injury or surgery should raise the suspicion of anaerobic infection of the central nervous system. I present a case of pneumocephalus associated with Bacteroides fragilis meningitis where the diagnosis was suspected after CT findings become available. Bacteroides fragilis meningitis is rare and often occurs in premature infants and neonates; only few cases are reported in adults. Pneumocephalus associated with Bacteroides fragilis meningitis is not described in the literature. This case also illustrates the absence of classic findings of meningeal irritation in the elderly. The literature is reviewed.